The development and implementation of an inter-professional simulation based pediatric acute care curriculum for ward health care providers. Issue 4 (July 2015) - Kotsakis, Afrothite; Mercer, Karen; Mohseni-Bod, Hadi; Gaiteiro, Rose; Agbeko, Rachel
Abstract An interprofessional, simulation based, acute care course for ward health care providers was developed and implemented with the objectives of teaching identification of deteriorating patients, practicing crisis resource management and basic life support skills, and using the SBAR (Situation Background Assessment Recommendation) communication tool. Thirty-eight physicians and 51 nurses attended the four separate courses. Nine questions on a 5-point Likert scale and two open-ended questions revealed that over 95% of respondents strongly agreed/agreed that facilitators encouraged active participation, lectures were presented in an interesting manner, and that simulations were useful for practical skills and for practicing communication. Open-ended questions revealed that participants felt more confident, understood the importance of communication, roles, teamwork and valued the day. Based on this evaluation, the program was regarded as feasible and acceptable to all health care providers.